STUDYING THE NEEDS OF FAMILIES RAISING CHILDREN WITH CEREBRAL PALSY - Munavvar Askarova (LIFE: International Journal of Health and Life-Sciences, 2025)
Raising a child with cerebral palsy (CP) is a complex task that requires significant physical, emotional, and financial resources. This article examines the basic needs of families raising children with cerebral palsy, including medical, psychological, social, and financial support. An initial study of the key problems faced by such families has been conducted and recommendations for their solution have been proposed.